Prediction models of iron level in beef muscle tissue toward ecological well-being - K. Narozhnykh (Global Journal of Environmental Science and Management)
BACKGROUND AND OBJECTIVES: Elemental status is associated with the biochemical processes occurring in the body. Beef, consumed worldwide, is an excellent source of iron in terms of quantity and bioavailability, providing up to 18 percent of the daily requirement. The level of iron in muscle tissue affects beef quality. Current methods used to assess iron content in cattle muscles are laborious and complex. Accordingly, the current study aimed to develop a fast and simple method to assess the elemental status of animals in vivo and in a minimally invasive way based on an effective model for iron-level prediction by using blood-analysis results toward ecological well-being. This method can overcome the shortcomings of currently used approaches.METHODS: Samples of diaphragmatic muscle weighing 100 grams, as well as blood samples, were obtained from Hereford cattle bred under typical conditions of an industrial complex in the south of Western Siberia, Russia. Elemental analysis was performed by atomic absorption method with electrothermal atomization. Regression analysis was conducted to estimate the relationships between iron level in the muscle tissue of Hereford cattle and independent values (blood parameters). An optimum model for predicting the iron level was established. The coefficients of regression models were calculated using the least squares method, and the values of the dependent variable corresponded with the Gaussian ones. A high correlation existed between independent variables.FINDINGS: An optimum model for predicting the iron level in the muscle tissue of Hereford cattle was established. It contained three predictors, namely, number of erythrocytes, color index, and globulin, as a result of selection based on internal and external-quality criteria. The model meets the necessary assumptions: the residuals are normally distributed, no autocorrelations exist, and the observations are influential. Furthermore, no signs of multicollinearity exist between the main effects of the model (variance-inflation factor = 1.2–1.7).CONCLUSION: The model can be used for the intravital analysis of iron level in the muscle tissue of cattle. In contrast to currently used methods, the approach proposed can be used for intravital analysis of the level of iron in muscle tissue, which is the most important advantage of the developed approach. The results can be used in ecology to assess ecological well-being and determine the allowable load of iron in animals. For veterinary medicine, the resulting model enables the evaluation of the iron level in the muscle tissue of Hereford cattle during their lifetime. Studying the effect of different factors on meat quality may allow to decrease or avoid useless measures used in farming, such as the excessive use of feed additives. In turn, these measures can decrease resource exploitation and increase farming productivity. Therefore, the results can guide the further development of sustainable farming.